Designing USU Student Center Post Pandemic COVID-19 with Tropical Architecture Approach - Andalucia Andalucia; Rafika Dewi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
University of Sumatera Utara (USU) is the one of the largest and the best universities in Medan which has full of facilities and infrastructure. Nevertheless, currently University of Sumatera Utara does not have a Student Center. The provision of a student center at a university is essential for the development of outstanding students. Furthermore, in the post pandemic COVID-19, humans need a healthier space or place to be live in. Activities that take place indoors require good air quality to prevent viruses from easily entering and thriving inside the room. The application of tropical architecture in the design of the USU Student Center is a consideration in creating a place suitable for post pandemic COVID-19 conditions, and it also serves as a solution for the climate in Indonesia.